Development of a Web-Based Free Homecoming Registration System by the Department of Transportation of South Sumatra Province - Sahfitri, Vivi (Jurnal Ilmiah Matrik, 2024)
This research aims to design and develop a web-based free homecoming registration system for the Department of Transportation of South Sumatra Province. The website is designed to assist administrators in managing and monitoring registrant data according to their travel routes, streamline the filtering process, and facilitate the storage and retrieval of large volumes of data. This improvement enables a more efficient registration process and accommodates an increasing number of participants each year. The development process employs Macromedia Dreamweaver 8 as the text editor, PHP as the programming language, phpMyAdmin for database management, and Google Chrome as the testing browser. The resulting website provides an integrated and user-friendly platform that enhances administrative efficiency and accessibility for registrants. The findings of this study are expected to contribute to better data management and service delivery within the Department of Transportation of South Sumatra Province